Disturbia - Marcus, Jackie; Medjuck, Joe.; Pollock, Tom.; Walsh, E. Bennett; Landon, Christopher, 1975-; Ellsworth, Carl.; Caruso, D. J.; LaBeouf, Shia, 1986-; Roemer, Sarah; Moss, Carrie-Anne, 1970-; Morse, David, 1953-; Yoo, Aaron; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2007)
Kale Brecht becomes a sullen, withdrawn, and troubled young man. He finds himself under a court-ordered sentence of house arrest. His mother, Julie, works night and day to support herself and her son. As the walls of his house begin to close in on Kale, he turns into a voyeur as his interests turn outside the windows towards those of his neighbors. Slowly, Kale begins to suspect his neighbor is a serial killer.
Title from container.
Special features: Deleted scenes; cast & crew commentary; outtakes; making of featurette; music video "Don't make me wait" by This World Fair.
Director of photography, Rogier Stoffers ; editor, Jim Page ; music, Geoff Zanelli ; costume designer, Marie- Sylvie Deveau ; production designer, Tom Southwell.
Shia LaBeouf, Sarah Roemer, Carrie-Anne Moss, David Morse, Aaron Yoo, Jose Pablo Cantillo, Matt Craven, Viola Davis.
MPAA rating: PG-13; for sequences of terror and violence, and some sensuality.
DVD.
Keywords: Home detention -- United States -- Drama; Voyeurism -- United States -- Drama; Mothers and sons -- United States -- Drama; Criminal behavior -- United States -- Drama; Suburbs -- United States -- Drama; Detencin̤ de personas -- Estados Unidos -- Teatro; Madre e hijo -- Estados Unidos -- Teatro; Thrillers (Motion pictures, television, etc.); Thriller -- Feature; Crime -- Feature; Suspense films